The influence of infant death on the nurse’s experience: Reflections in the light of phenomenology - da Silva, Jéssica Íris Franco; da Silva, Hallyson Leno Lucas; Carneiro, Shayanna Mickaela Duque; de Alencar, Isabele Gouveia Muniz; de Medeiros, Katarine Florêncio; e Araújo, Rhayssa de Oliveira; de Oliveira, Jonas Sâmi Albuquerque (Seven Editora, 2023)
There are numerous positive and negative factors that influence the experience of nurses, especially those of a psychic and/or emotional nature, which can manifest themselves in various ways in the professional and even personal trajectory. To understand this experience in pediatric intensive care settings, appropriating the systematics involved in the relationship with children and families, it is necessary to reflect on the influence that infant death can have on this work. This study aimed to reflect on the influence of infant death on the experience of nurses, in the light of phenomenology. This is a qualitative study of the reflective essay type, with phenomenological inspiration, using aspects of the works of Merleau-Ponty, carried out from a dialogue between the scientific literature and the critical analysis of the authors. Each person experiences particular perceptions and sensations, including in the reality of intensive care settings. Professionals acquire special meanings in professional and personal life, because they are prepared for everyday situations of their work, and still have the opportunity to reflect on this world that surrounds them. The reflections demonstrated how the experiences with death infer values to the social role that the nurse routinely translates, considering her humanized attitude as a principle very well applied in reality, and how this set of her various perceptions and sensations have repercussions on the care provided. DOI:https://doi.org/10.56238/innovhealthknow-027